2020
DOI: 10.1186/s12883-020-01841-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis to evaluate the diagnostic accuracy of recognition of stroke in the emergency department (ROSIER) scale

Abstract: Background The present study aims to evaluate the performance and the clinical applicability of the Recognition of Stroke in the Emergency Department (ROSIER) scale via systematic review and meta-analysis. Methods Electronic databases of Pubmed and Embase were searched between 1st January 2005 (when ROSIER developed) and 8th May 2020. Studies that evaluated the diagnostic accuracy of the ROSIER scale were included. The sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…In 2019, the assessment of both cortical and motor function using the Rapid Arterial Occlusion Evaluation Scale (RACE), Field Assessment Stroke Triage for Emergency Destination (FAST-ED) and National Institute of Health stroke scale (NIHSS) showed the best diagnostic accuracy values for selecting subjects with large vessel occlusion (LVO) (22). In 2020, a systematic review and meta-analysis revealed that ROSIER was a valid scale with high clinical applicability (23). Even though numerous scales have emerged for assessing the stroke, only a few studies compared the Se and Sp between FAST and BEFAST.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the assessment of both cortical and motor function using the Rapid Arterial Occlusion Evaluation Scale (RACE), Field Assessment Stroke Triage for Emergency Destination (FAST-ED) and National Institute of Health stroke scale (NIHSS) showed the best diagnostic accuracy values for selecting subjects with large vessel occlusion (LVO) (22). In 2020, a systematic review and meta-analysis revealed that ROSIER was a valid scale with high clinical applicability (23). Even though numerous scales have emerged for assessing the stroke, only a few studies compared the Se and Sp between FAST and BEFAST.…”
Section: Discussionmentioning
confidence: 99%
“…The Recognition of Stroke in the Emergency Room (ROSIER) scale adalah skala yang valid dengan penerapan klinis yang tinggi, yang tidak hanya memiliki akurasi diagnostik yang baik di Eropa tetapi juga menunjukkan kinerja yang sangat baik di Asia. Selain itu, skala ROSIER menunjukkan penerapan yang baik dalam pengaturan pra-rumah sakit dengan tenaga medis terlatih (Han et al, 2020). ROSIER scale memberikan manfaat dalam evaluasi stroke di lingkungan pra-rumah sakit.…”
Section: Pembahasanunclassified
“…Therefore, distinguishing hemorrhagic stroke from ischemia stroke has an important implication for EMS. Some prehospital stroke scales were used for EMS to identify stroke in recent studies, such as the Face Arm Speech Test (FAST), Los Angeles Prehospital Stroke Screen (LAPSS), and Recognition of Stroke in the Emergency Room (ROSIER), parts of which had moderateto-good sensitivity and the lower levels of specificity [9][10][11][12]. In addition, some studies have proved that serum markers had a certain advantage in distinguishing hemorrhagic stroke and ischemic stroke, including glial fibrillary acidic protein (GFAP), N-terminal proB-type natriuretic peptide (NT-proBNP), and retinol-binding protein 4 (RBP-4) [13,14].…”
Section: Introductionmentioning
confidence: 99%